Impact of Entrepreneurial Inspiration, Awareness, and Skills on University Students’ Entrepreneurial Intentions: The Mediating Role of Entrepreneurial Education - Ghulam Mujtaba; Siti Nur ‘Atikah Zulkiffli; Siti Falindah Padlee; Wan Norhayati Mohamed; Najahul Kamilah Aminy Sukri (Administrative Sciences)
In the pursuit of development and evaluation, entrepreneurship is the key to unlocking the shackles of poverty and unemployment. However, Pakistani students often catch themselves lacking the catalyst that ignites the entrepreneurial flame due to the absence of the essential knowledge, skills, and creative mindset, which can lead to significant challenges and a dim attitude toward entrepreneurial intentions. The harsh reality is that the rate of new business formation in Pakistan is only 1.5%. Therefore, the study aims to shed light on the impact of entrepreneurial inspiration, entrepreneurial skills, and entrepreneurial awareness on the intentions of Pakistani university students with the mediating effects of entrepreneurial education. Revealing the importance of entrepreneurial education in shaping the minds and desires of the students, seven hypotheses were developed based on social cognitive theory (SCT). A comprehensive survey was used to collect primary data from final-year business students, with a sample size of 865, from seven universities in the Punjab region of Pakistan that provide higher education in entrepreneurship and the data were analyzed in two stages, namely a model measurement and structural model Via Smart PLS 4. The findings clearly augment entrepreneurial inspiration, entrepreneurial skills, and entrepreneurial awareness, which can ignite the flames of entrepreneurship among Pakistani students. Moreover, entrepreneurial education plays a crucial role in mediating relationships and motivating students to choose entrepreneurship as a future occupation. However, the study is restricted to the Punjab region of Pakistan and focuses solely on final-year business students. This study serves as a guiding light of hope for academics, policymakers, and educational institutions to emphasize the need to revamp the business education landscape in Pakistan to foster entrepreneurial passion among our future leaders.